Essays in sociology and social philosophy - "Ginsberg, Morris" (Middlesex, 1968)
This book contents the following topics: The problems and methods of sociology; The individual and society; The idea or progress: a Revaluation; Social Change; National Character; Antisemitism; The life and Work of Edward Westermarck; On the diversity of Morals; Reason and Experience in Ethics.
Keywords: Sociology